Tooth Decay in the Perspective of Nutritional Status - Sri Nuryati; Siti Sab’atul Habibah; Danan Danan (Poltekkes Kemenkes Kupang, 2024)
Optimal nutritional intake impacts a child’s physical growth and development, including their oral and dental health. Adequate protein and mineral intake influence the growth of primary teeth. This study aims to describe the relationship between tooth decay and nutritional status among first-grade students at SDN 3 Guntung Manggis, Banjarbaru City. The research employs a descriptive study design with a cross-sectional approach. Samples were selected using the Proportional Random Sampling technique, with a total of 92 students as respondents. The results indicate that the majority of respondents had good nutritional status (70.6%), while some were overnourished (14.1%) or obese (10.9%). Most respondents exhibited a high level of tooth decay (53.3%). Cross-tabulation analysis revealed that all nutritional status categories were predominantly associated with high tooth decay, with the highest proportion observed in the obese group, where 60% of obese students experienced severe tooth decay. In conclusion, obese students tend to be more vulnerable to tooth decay. Future research is suggested to use analytical methods and increase the sample size.